“I’ve got this hole…”: Experiences of therapist involuntary childlessness with clients in therapeutic practice - Stokley, Martin; Sanders, Val (European Journal for Qualitative Research in Psychotherapy, 2019)
Little has been written on how therapists experience their practice in relation to involuntary childlessness. There have been no systematic research projects exploring solely the therapist’s voice on this issue to date with only two pieces of literature specifically discussing therapist involuntary childlessness in professional practice. This research explores the lived experience of qualified therapists regarding involuntary childlessness in therapeutic practice filling the gap in the existing literature. Four female participants were recruited through an initial online survey and they completed an audio recorded semi-structured interview. One of the researchers also completed a written self-interview to add a missing male voice to the research. Interpretative Phenomenological Analysis was used to analyse all five interviews. Three main themes were identified: ‘Experience of own childlessness in work with clients’, ‘Therapist childlessness beyond client work’, and ‘Therapist childlessness and theory’. This article concentrates on explicating the main theme ‘Experience of own childlessness in work with clients’ with the further two main themes being the subject of a future article. Findings indicate that therapist involuntary childlessness cannot be separated from therapeutic practice and greater awareness of the potential proactive countertransference is needed. In addition, issues around client judgement, implicit self-disclosure, and the potential positive benefit of vicarious parenthood are considered.